The effect of Asparagopsis taxiformis, Ascophyllum nodosum, and Fucus vesiculosus on ruminal methanogenesis and metagenomic functional profiles in vitro - Timur Yergaliyev; Susanne Künzel; Anna Hanauska; Antonia Rees; Katharina J. Wild; Ásta H. Pétursdóttir; Helga Gunnlaugsdóttir; Christopher K. Reynolds; David J. Humphries; Markus Rodehutscord; Amélia Camarinha-Silva (Microbiology Spectrum, 2024)
ABSTRACT The ruminant-microorganism symbiosis is unique by providing high-quality food from fibrous materials but also contributes to the production of one of the most potent greenhouse gases—methane. Mitigating methanogenesis in ruminants has been a focus of interest in the past decades. One of the promising strategies to combat methane production is the use of feed supplements, such as seaweeds, that might mitigate methanogenesis via microbiome modulation and direct chemical inhibition. We conducted in vitro investigations of the effect of three seaweeds (Ascophyllum nodosum, Asparagopsis taxiformis, and Fucus vesiculosus) harvested at different locations (Iceland, Scotland, and Portugal) on methane production. We applied metataxonomics (16S rRNA gene amplicons) and metagenomics (shotgun) methods to uncover the interplay between the microbiome’s taxonomical and functional states, methanogenesis rates, and seaweed supplementations. Methane concentration was reduced by A. nodosum and F. vesiculosus, both harvested in Scotland and A. taxiformis, with the greatest effect of the latter. A. taxiformis acted through the reduction of archaea-to-bacteria ratios but not eukaryotes-to-bacteria. Moreover, A. taxiformis application was accompanied by shifts in both taxonomic and functional profiles of the microbial communities, decreasing not only archaeal ratios but also abundances of methanogenesis-associated functions. Methanobrevibacter “SGMT” (M. smithii, M. gottschalkii, M. millerae or M. thaueri; high methane yield) to “RO” (M. ruminantium and M. olleyae; low methane yield) clades ratios were also decreased, indicating that A. taxiformis application favored Methanobrevibacter species that produce less methane. Most of the functions directly involved in methanogenesis were less abundant, while the abundances of the small subset of functions that participate in methane assimilation were increased.IMPORTANCEThe application of A. taxiformis significantly reduced methane production in vitro. We showed that this reduction was linked to changes in microbial function profiles, the decline in the overall archaeal community counts, and shifts in ratios of Methanobrevibacter “SGMT” and “RO” clades. A. nodosum and F. vesiculosus, obtained from Scotland, also decreased methane concentration in the total gas, while the same seaweed species from Iceland did not.